Features of Body Language and Its Applications in Postmodern Ceramics: Fitur Bahasa Tubuh dan Aplikasinya dalam Keramik Postmodern - Abdulhafedh, Omar Mohmdsamer (Academia Open, 2024)
All visual arts in the post-modern era, including ceramics, have a language that forms features and connotations. Therefore, the researcher studied these features and divided them into an introduction that included the research problem, which is clear from the following question: What are the features of body language and its applications in post-modern ceramics? This is of cognitive importance as it provides an objective study for researchers in ceramic plastic sciences. In addition, the aim of the research is to reveal the features of body language and its applications in post-modern ceramics. As for the materials and methods, they included the limits of the research, its variables, and the theoretical framework that shows these variables and how these features were linked. The framework concluded with the most important indicators that resulted from the theoretical framework. The research also included the procedures related to the research sample, the research tool, and the sample analysis. Finally, the research included the results and conclusions, followed by the sources that the researcher used to complete his research. Highlight: Post-modern ceramics reflect features and connotations of body language. Research explores theoretical framework, variables, and applications in ceramic sciences. Results reveal key indicators, conclusions, and supporting references. Keywords: Countenance, body language, postmodernism